Identification Of Morphology, Growth Kinetic And Secondary Metabolites Synthesized In Green Freshwater Microalgae (Coccomyxa Dispar) - Joey Lew Hui, Lin (Pusat Pengajian Teknologi Industri, 2020)
Microalgae are considered a promising source of organism that can be cultured and isolated to obtain a range of functional metabolites. They are renewable, easily to be cultured and have short generation time which overcome land limitation problem caused by utilization of plant resources. Their metabolites can be used as a source of natural ingredients in pharmaceutical and nutraceutical products. This study aims to analyse potential metabolites in freshwater microalgae, Coccomyxa dispar in BBM medium with pH 3.3. The cultivation was carried out in room temperature with light intensity 1500 lux and aerated for 24 hours.